The Impact Of Crude Paalm Oil (CPO) Prices on The Prices of Fresh Fruit Bunches (FFB) in Riau Provinces - Razak, Abdul; Apriyanto, Mulono; Ariyanto, Anto (Jurnal Mamangan, 2024)
This study will look at trends in FFB prices, CPO prices, currency rates, and CPO exports. Then, we'll look at how FFB pricing, CPO prices, and exchange rates affect CPO exports. Both quantitative and descriptive analysis are the analytical techniques employed. Time Series data for the years 2014–2024 comprise the secondary data used in this study. Data sources for this study include the Riau Province Central Statistics Agency, Indonesian Palm Oil Farmers Association (APKASINDO), the Riau Province Plantation Service. The Error Correction Model (ECM) analysis approach was utilized. The study's findings indicate that: (1) CPO export growth, FFB prices, CPO prices, and exchange rates all have a tendency to vary annually. (2) Both in the short and long run, CPO exports are positively and significantly impacted by the FFB price and CPO pricing variables. (3) Both in the short and long term, CPO exports are positively impacted by the exchange rate variable, though not significantly.